Dean Worcester's Fantasy Islands : Photography, Film, and the Colonial Philippines - Rice, Mark (Book collections on Project MUSE., 2014)
"Informed by contemporary theories of colonial photography and the history of U.S. imperialism, Dean Worcester's Fantasy Islands--a product of intensive archival research at the University of Michigan and elsewhere--is narrative in its approach, tracing Worcester's emergence both as a colonial administrator and a photographer and analyzing the intersections between his personal desires and his political agenda as they shaped his photography in the Philippines. Author Mark Rice discusses the controversies that surrounded Worcester's use of evocative photography and demonstrates his lasting influence on dominant modes of ethnographic photography as seen in the pages of National Geographic and elsewhere"--